“Gestión de la comunicación organizacional en la sección administrativa de un Centro Educativo. Estudio del caso Escuela Particular Mixta Bilingüe Antonio Lorenzo de Lavoisier” - Romero Aguas, Lizbeth Nathaly (2013)
The research comprises three chapters. In the first the concepts and categories of corporate communication processes, elements, networks and typologies described. In the second chapter of detailed diagnosis of the management of organizational communication. In the third chapter of the research has an internal organizational determining the strategies proposed. As the final chapter of the research, conclusions and recommendations have practically and theoretical